PENINGKATAN HASIL BELAJAR DENGAN MENERAPKAN PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA BONGKAR PASANG MATERI BANGUN DATAR KELAS VII SMP - Magdalena Florensia Dua Soba; Finsensius Yesekiel Naja; Ningsih Ningsih (Program Studi Pendidikan Matematika, 2021)
This study aims to determine: (1) student activities in cooperative learning type STAD with the assistance of unloading rectangular material in class VII SMPK Alvarez Paga;(2) student learning outcomes on rectangular material in class VII SMPK Alvarez Paga through the application of the STAD type cooperative learning model assisted by the loading and unloading media. The type of research used is Classroom Action Research (PTK) which is conducted in two cycles. Each cycle has four stages of activity, namely: planning, implementing, observing, and reflecting. Data collection techniques used in this study were observation, tests, and documentation. The subjects in this study were students of class VII SMPK Alvarez Paga with 18 students consisting of 8 boys and 10 girls. Data analysis using observational data analysis techniques and data analysis techniques learning outcomes. The results of this study indicate the cooperative learning model type STAD with the assistance of unloading learning media can increase learning activities and learning outcomes of class VII students of SMPK Alvarez Paga.